2021
DOI: 10.1016/j.solmat.2021.111034
|View full text |Cite
|
Sign up to set email alerts
|

Thinned GaInP/GaInAs/Ge solar cells grown with reduced cracking on Ge|Si virtual substrates

Abstract: Reducing the formation of cracks during growth of GaInP/GaInAs/Ge 3-junction solar cells on Ge|Si virtual substrates has been attempted by thinning the structure, namely the Ge bottom cell and the GaInAs middle cell. The theoretical analysis performed using realistic device parameters indicates that the GaInAs middle cell can be drastically thinned to 1000 nm while increasing its In content to 8% with an efficiency loss in the 3-junction cell below 3%. The experimental results show that the formation of macros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The theoretical analyses and fits to experimental data are primarily based on the Scattering Matrix Method to analyze the optical processes and on the Hovel model to calculate the photocurrents and recombination currents, as detailed elsewhere [1]- [2][3]. III-V structures are grown by metal-organic chemical vapor deposition (MOCVD) using standard precursors [3].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The theoretical analyses and fits to experimental data are primarily based on the Scattering Matrix Method to analyze the optical processes and on the Hovel model to calculate the photocurrents and recombination currents, as detailed elsewhere [1]- [2][3]. III-V structures are grown by metal-organic chemical vapor deposition (MOCVD) using standard precursors [3].…”
Section: Methodsmentioning
confidence: 99%
“…Thick Ge layers are deposited by reduced pressure chemical vapor deposition (RP-CVD) [3] and ultrathin Ge films are deposited by radio-frequency, plasma-enhanced chemical vapor deposition (RF-PECVD), using the process parameters explained elsewhere [4]. 0.1 cm 2 solar cells are manufactured using standard photolithography techniques and gold-based metal stacks, except for Si that uses a Pd/Ti/Pd/Al system (details in [1]). III-V MJSC Designs a) GaInP/GaInAs/Ge|Si with Active Ge Bottom Cell.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tandem solar cells of III-V semiconductors can achieve the maximum efficiency, which benefits by an efficient utilization of the solar spectrum and lattice match. Especially, the case of Ge-based III-V triple-junction (TJ) solar cells [1][2][3][4][5] have attracted much attention, which has been widely applied in space for energy supply. To confine the misfit dislocation and minimize the strain, the previous study reported 6 that multijunction (MJ) III-V devices use compositionally graded buffers, which have demonstrated solar-to-electrical conversion efficiency of 39.2% (1 sun AM1.5G).…”
Section: │ Introductionmentioning
confidence: 99%